WHAT IF MARX AND VEBLEN MET… - Araz Takay, Bahar; Güler Aydın, Derya (Economic Annals, 2014)
The aim of this study is to analyse both the differences and the similarities between Marx and Veblen regarding historical specificity, evolution, and alienation. Starting with their discussions on these subjects, this article builds on the analyses of capitalism. The goal of this study is not to collapse Marx and Veblen into one another but rather to understand capitalism by presenting the complementary relationship of the two economists’ analyses and to introduce an appropriate analytical framework for understanding capitalism. This study consists of three parts. The first part examines how Veblen regarded Marx’s analysis, and how Marx especially viewed Darwin’s theory of evolution. Marx’s approach to evolution and Veblen’s criticism of Marx on this topic will constitute the general framework of this part. The second part of the study evaluates the level of agreement or disagreement between Veblen and Marx on the idea of historicism from the perspective of dialectical materialism. The last part a alyses Marx and Veblen’s different ideas of the concept of alienation. The two economists’ views on the capitalist system will be determined based on these three concepts, introducing the similarities between them as well as the differences.